Temporal Release and Denature of Several Mediators in Pure Platelet-Rich Plasma and Temperature-Induced Platelet Lysates Derived from a Similar Bovine Platelet Concentrate - Jorge U. Carmona; Catalina López; Alejandro Ceballos-Márquez (Veterinary Medicine International)
There is scarce information about bovine platelet-rich plasma/platelet-rich gel (PRP/PRG) and related hemocomponents (HCs), such as platelet lysates (PLs), including growth factor (GF) and cytokine concentrations, and how the stability of these biomolecules could be affected by time and temperature. This study aimed to evaluate the release and stability of transforming growth factor beta 1 (TGF-β1), interleukin 4 (IL-4), and tumor necrosis factor alpha (TNF-α) contained in bovine pure PRP (P-PRP) and temperature-induced PL (TIPL) coming from a similar platelet concentrate (PC) at 4 and 37°C at 3 and 96 h. Platelet concentrates (PCs) presented a 1.7-fold concentration of platelets (PLTs) with negligible counts of white blood cells (WBCs) when compared to the counts for these cells in whole blood. TGF-β1 concentrations were significantly lowest in plasma followed by TIPL, chemical-induced PL (CIPL), and P-PRP. IL-4 and TNF-α concentrations did not differ between HCs. TGF-β1 concentrations were negatively affected in P-PRPs stored at 4°C at 3 and 96 h, whereas those from P-PRP maintained at 37°C presented similar concentrations to TIPL stored at both temperatures over time. IL-4 and TNF-α concentrations were not affected by time or temperature in any of the HCs evaluated. Pure PRGs released additional quantities of GF and cytokines over time when compared with HCs stored over 96 h at 4 and 37°C. The method, either chemical or physical, used for platelet activation or damage produces a different GF and cytokine release pattern, which makes to each evaluated HCs different despite they come from a similar bovine PC. P-PRP activated with calcium gluconate and maintained at 37°C, which polymerizes in P-PRG, showed the best GF and cytokine release/denature profile compared with the rest of the HCs evaluated.